Assessment of Soil Chemical Fertility Status in Wukirsari Sub-District, Cangkringan, Sleman, Special Region of Yogyakarta : Kajian Status Kesuburan Kimia Tanah di Kalurahan Wukirsari, Kapanewon Cangkringan, Kabupaten Sleman, Daerah Istimewa Yogyakarta - Fransisca, Ema; Amiadji Julianto, Eko (Universitas Pembangunan Nasional Veteran Yogyakarta, 2025)
Agricultural productivity is influenced by soil fertility, which depends on the nutrient content of the soil as well as the land use and management practices applied. The objective of this study is to identify the chemical properties of the soil, determine its chemical fertility status, and analyzed limiting factors. The research was conducted from December 2024 to February 2025 using survey methods and laboratory analysis according to the criteria of the Soil Research Center (1995). Representative sample points were determined by purposive method on the overlay results of thematic maps (Land Use Maps, Slope Maps, Elevation Maps) and resulted in 12 Land Units. The analysis results showed that the Cation Exchange Capacity (CEC) values range from 2,2 - 7,55 cmol (+)/kg classified as very low to low, Base Saturation (BS) ranges from 56,24 - 99,99% categorized as high to very high, P2O5 was 59,66 - 88,37 mg/100g classified as high to very high, K2O was 2,09 - 15,51 mg/100g categorized as very low to low, C-organic was 0,46 – 2,38% classified as low to moderate, and pH H2O was 4,83 – 7,7 indicating acidic to slightly alkaline conditions therefore the status of soil chemical fertility obtained 2 status, very low covering an area of 373,19 ha (39,42%) and low covering 600,09 ha (60,58%). The low fertility status is mainly influenced by the low Cation Exchange Capacity, content of K2O, and Organic Carbon.